A Simple and Improved Model for Describing Soil Hydraulic Properties from Saturation to Oven Dryness - Liao, K. (2020)
In addition, the Morris method was applied to quantify the parameter sensitivity of the new model. Results showed that M2 to M5 gave slightly better performance than M1 in predicting soil water retention characteristics, with a decrease of ∼15% in the root mean squared error (RMSE). However, they produced substantially better performance than M1 in estimating soil hydraulic conductivities, with a decrease of ∼40% in the RMSE. The new model with all of the model parameters being fitted (M2) was more efficient than those with one or two model parameters not fitted. However, an over‐parameterization problem was detected with M2. Physically unrealistic parameters (e.g., the saturated soil water content and effective grain diameter) exist in M2. These parameters were found to have important influences on the results of the soil hydraulic properties prediction based on the Morris‐based sensitivity analysis. Overall, the new model with two parameters not fitted (M5) can best describe the soil hydraulic properties from saturation to oven dryness and had the potential to simulate water and solute transport in the vadose zone.